Role of dynamic sentinel node biopsy in carcinoma penis with or without palpable nodes - Kathiresan, N. (Indian J Urol, 2016)
INTRODUCTION: We aimed to evaluate the role of dynamic sentinel node biopsy (DSLNB) in patients diagnosed with carcinoma penis and clinically N0 disease using superficial inguinal dissection as the standard staging modality. MATERIALS AND METHODS: Twenty consecutive men (40 groins) with carcinoma penis having clinically N0 status were enrolled in the study. Patients underwent DSLNB if fine needle aspiration cytology from the groin nodes was negative, followed by injection of radiocolloid and blue dye. The sentinel lymph node(s) were harvested. The inguinal incision was then extended and a modified superficial inguinal dissection was performed and all nodes were labeled separately and sent for frozen section. A completion deep inguinal with pelvic dissection was performed if any of the nodes were reported positive for malignancy. RESULTS: The median age of the patients was 52.5 years. Ten patients were smokers. Phimosis was present in five patients. Lesions were present over the glans penis and shaft in 18 and two patients, respectively. Wide local excision, partial penectomy and total penectomy were performed in one, 15 and four patients, respectively. Clinically palpable nodes were found in 19 groins. Median follow-up was 26 months. Nodes were positive in 10 groins. DSLNB missed the sentinel node in one groin. The accuracy and false-negative rate of DSLNB was 97.5% and 10%, respectively. CONCLUSION: DSLNB is a useful and reliable technique to identify the involved node(s) in patients diagnosed as having carcinoma penis with clinical N0 status (with or without palpable nodes). It helps to avoid the morbidity associated with a staging inguinal dissection in these patients.